Characteristics and risk factors of retinal vasculopathy in antiphospholipid syndrome. (February 2022) - Xie, Zhijuan; Li, Hui; Qi, Wanting; Li, Jing; Wu, Chanyuan; Hu, Chaojun; Jiang, Nan; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Jiuliang; Sui, Ruifang; et al.
Background: Retinal vasculopathy including retinal artery occlusion (RAO) or retinal vein occlusion (RVO) was recently found to occur more frequently in antiphospholipid syndrome (APS) patients than non-APS patients. This study aims to investigate the clinical manifestation and risk factors of retinal vasculopathy among APS patients. Methods: In this single-center prospective cohort study, we evaluated APS patients with or without retinal vasculopathy during 2018–2020 at Peking Union Medical College Hospital. Clinical variables were compared, and a logistical regression model was built to explore risk factors. Hierarchical cluster analysis using Euclidean distances was applied to identify clusters of variables. Results: A total of 310 APS patients (67.4% female, mean age 38.1 years) were included, of whom 18 (5.8%) were diagnosed with retinal vasculopathy (9 with RVO and 9 with RAO). No significant differences were found among most demographic characteristics, clinical manifestations, or antibody profiles. APS-related heart valve disease (odds ratio OR 13.66, 95% confidence interval CI 4.55–40.98), APS nephropathy (OR 12.77, 95% CI 4.04–40.35), and thrombocytopenia (OR 2.63, 95% CI 1.01–6.89) were predictive of retinal vasculopathy. APS-related heart valve disease and nephropathy were also found to be statistically significant predictors in multivariate logistical regression analysis. Non-criteria manifestations were aggregated with retinal vasculopathy from a cluster analysis of variables. Conclusion: Patients with APS-related heart valve disease and nephropathy suffered a higher risk of retinal vasculopathy. The underlying mechanisms of aPL-associated retinal vasculopathy may involve thrombotic microangiopathy, leading to poor prognosis and therapeutic changes.